2023
DOI: 10.3389/fnut.2023.1118923
|View full text |Cite
|
Sign up to set email alerts
|

Hypolipidemic mechanism of Pleurotus eryngii polysaccharides in high-fat diet-induced obese mice based on metabolomics

Abstract: ObjectiveIn this study, the structure of Pleurotus eryngii polysaccharides (PEPs) was characterized, and the mechanism of PEP on obesity and hyperlipidemia induced by high-fat diet was evaluated by metabonomic analysis.MethodsThe structure of PEPs were characterized by monosaccharide composition, Fourier transform infrared spectroscopy and thermogravimetry. In animal experiments, H&E staining was used to observe the morphological difference of epididymal adipose tissue of mice in each group. Ultrahigh … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Some people may have muscular toxicity after taking statins, and rhabdomyolysis occurs in severe cases (He et al, 2018). Edible fungi polysaccharides can improve lipid metabolism disorders mainly by inhibiting or promoting the expression of related lipid metabolism enzymes and related factors, improving the activity of bile acid synthesis, regulating intestinal flora, and alleviating oxidative stress reaction (Yin et al, 2020; Zhao et al, 2023). Flavonoids can promote the decomposition of cholesterol and triglyceride to improve liver function and lipid metabolism (Huiming et al, 2022; Lanlan et al, 2022).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Some people may have muscular toxicity after taking statins, and rhabdomyolysis occurs in severe cases (He et al, 2018). Edible fungi polysaccharides can improve lipid metabolism disorders mainly by inhibiting or promoting the expression of related lipid metabolism enzymes and related factors, improving the activity of bile acid synthesis, regulating intestinal flora, and alleviating oxidative stress reaction (Yin et al, 2020; Zhao et al, 2023). Flavonoids can promote the decomposition of cholesterol and triglyceride to improve liver function and lipid metabolism (Huiming et al, 2022; Lanlan et al, 2022).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…An HFD reduced serum ADP concentrations in golden hamsters, while GLF‐217 maintained and stimulated ADP secretion, thereby reducing the incidence of atherosclerosis. The relative constancy of blood lipids in the body mainly depends on the regulatory effect of the liver cells, the liver cells damage inevitably leads to abnormal lipid synthesis and metabolism in the body (Zhao et al, 2023). Experimental results show that long‐term HFD will bring more serious damage to liver and increase the risk of forming fatty liver, and GLF‐217 can alleviate the liver damage caused by HFD, in addition, we found that LOV intervention caused more severe the liver damage in golden hamsters than that in the GLF‐217 group, and the ALT level in LOV group was significantly higher than that in the HFD group.…”
Section: Discussionmentioning
confidence: 99%
“…The basic structural components of cell membranes are glycerophospholipids and sphingolipids, and Lysophosphatidylcholine (lysoPCs) is generated by the hydrolysis of oxidized phosphatidylcholine in LDL by phospholipase A2 and act in a range of biological processes ( Ren et al, 2023 ; Zhao et al, 2023 ). Phosphatidylcholine (PC), phosphatidylglycerol (PG), and phosphatidylethanolamine (PE) are the three types of glycerophospholipids ( Rowlett et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%